Equity valuation of PUMA SE - Arndt, Fabian (2019)
The purpose of the dissertation is to determine a target price per share for the sportswear pro-ducer PUMA SE that is listed on the German MDAX. Based on this value and relative to the current market price, a buy, hold or sell recommendation is provided. Hence, the underlying research question of this dissertation is: “What is the fair value per share for PUMA SE on 31 December 2018 and the implied investment recommendation on 13 February 2019?”. The ob-tained share price is based on a combination of two valuation methods: The discounted cash flow model and a relative valuation approach based on multiples that result in a price per share of €505.91. The valuation is an outcome of a comprehensive market, industry and company analysis. By comparing the computed share price with the current market price of €481.50 as of 13 February 2019, a hold recommendation with upside potential of 5.07% is issued. Finally, selected assumptions and results are compared with the equity report of PUMA SE from War-burg Research. All information and data in this publication stem from publicly available sources.